Culture and customs of Serbia and Montenegro - Deliso, Christopher 1974- (Greenwood Press, 2009)
Product Description: With their recently declared independence from one another in the aftermath of the breakdown of the USSR, Serbia and Montenegro are coming into their own, all while keeping their long histories of traditions and customs alive and growing. A blend of Eastern traditions with European cultures provides a unique foundation for these Balkan countries. Narrative chapters examine every day contemporary life in Serbia and Montenegro, focusing on topics such as daily religious practices, gender roles, family life, cuisine, fashion, literature, art and architecture, and more. This volume is the perfect addition to high school and public libraries, and is even ideal for college students studying abroad.
Includes bibliographical references and index
Keywords: Alltag, Brauchtum; Landeskunde; Serbia -- Civilization; Montenegro -- Civilization; Serbia -- Social life and customs; Montenegro -- Social life and customs; Montenegro; Serbien